Hydrogeochemical characteristic of thermal waters in Bańska Niżna - Korzec, Klaudia (Geology, Geophysics and Environment, 2016)
Thermal waters are one of the greatest treasures of the Podhale. They are used not only in heat engineering but also in recreation, medicine and rehabilitation (Kępińska, 2004, 2009; Tomaszewska, 2009). It is also known that thermal waters are treated and used for drinking or commercial purposes (Bujakowski & Tomaszewska, 2007; Tomaszewska, 2009, 2011; Tomaszewska & Bodzek, 2012). Thermal waters in Bańska Niżna are exploited by PEC Geotermia Podhalańska S.A. company. Commercial use of these waters began in 1993, when the system based on geothermal doublet, supplied heat to several houses (Ślimak & Wartak, 2009). Currently, the exploitation is made by using three wells: Bańska IG-1 well, Bańska PGP-1 well and Bańska PGP-3 well.Hydrogeochemical characteristic of thermal waters in Bańska Niżna was based on researches concerning the state of those waters, which was being carried out every two weeks between December 2013 and August 2015. Field research was based on measurements of non-stable parameters - pH, electrical conductivity γ25 and the temperature on the flow. The results of field measurements were supplemented with archival data: water temperature at the well head, pressure and well discharge.The samples for laboratory tests were taken by the author of this work in accordance with the standard ISO 5667-11: 2004. The chemical composition analysis of thermal waters was carried out by accredited Hydrogeochemical Laboratory of the Department of Hydrogeology and Engineering Geology AGH in Kraków (certificate of Polish Centre of Accreditation No. AB 1050). This analysis included measurements of concentration of 45 indicators. On the basis of the results of the research, the hydrogeochemical type of thermal waters in Bańska Niżna was defined as sulfate-chloride-sodium-calcium type (according to the classification by Szczukariew-Prikłoński).The medium values of the basic parameters of analyzed wells, estimated on the basis of data from 2013-2015, are as follows:- Bańska IG-1 well: pH 6,63,